Experiencia y muerte según Rodrigo Fresán - Martín Lombardo (Caravelle)
This article proposes a reading of the Argentinean writer Rodrigo Fresán’s work, and more specifically of two of his novels Mantra and Jardines de Kensington. The work analyzes the ways in which the author represents the ideas of death and experience. At the same time, it studies the particular way in which he builds his tales.